The obscuration by dust of most of the growth of supermassive black holes. - Martínez-Sansigre, A; Rawlings, S; Lacy, M; Fadda, D; Marleau, F; Simpson, C; Willott, C; Jarvis, M (2005)
Supermassive black holes underwent periods of exponential growth during which we see them as quasars in the distant Universe. The summed emission from these quasars generates the cosmic X-ray background, the spectrum of which has been used to argue that most black-hole growth is obscured. There are clear examples of obscured black-hole growth in the form of 'type-2' quasars, but their numbers are fewer than expected from modelling of the X-ray background. Here we report the direct detection of a population of distant type-2 quasars, which is at least comparable in size to the well-known unobscured type-1 population. We selected objects that have mid-infrared and radio emissions characteristic of quasars, but which are faint at near-infrared and optical wavelengths. We conclude that this population is responsible for most of the black-hole growth in the young Universe and that, throughout cosmic history, black-hole growth occurs in the dusty, gas-rich centres of active galaxies.